Insights Into the Mechanisms Implicated in Pinus pinaster Resistance to Pinewood Nematode - Modesto, Inês; Sterck, Lieven; Arbona, Vicent; Gómez-Cadenas, Aurelio; Carrasquinho, Isabel; Van de Peer, Yves; Miguel, Célia M. (Frontiers in Plant Science, 2021)
Pine wilt disease (PWD), caused by the plant-parasitic nematode Bursaphelenchus xylophilus, has become a severe environmental problem in the Iberian Peninsula with devastating effects in Pinus pinaster forests. Despite the high levels of this species’ susceptibility, previous studies reported heritable resistance in P. pinaster trees. Understanding the basis of this resistance can be of extreme relevance for future programs aiming at reducing the disease impact on P. pinaster forests. In this study, we highlighted the mechanisms possibly involved in P. pinaster resistance to PWD, by comparing the transcriptional changes between resistant and susceptible plants after infection. Our analysis revealed a higher number of differentially expressed genes in resistant plants (1916) when compared with susceptible plants (1226). Resistance to PWN is mediated by the induction of the jasmonic acid defense pathway, secondary metabolism pathways, lignin synthesis, oxidative stress response genes and resistance genes. Quantification of the acetyl bromide-soluble lignin confirmed a significant increase of cell wall lignification of stem tissues around the inoculation zone in resistant plants. In addition to less lignified cell walls, susceptibility to the pine wood nematode seems associated with the activation of the salicylic acid (SA) defense pathway at 72 hpi, as revealed by the higher SA levels in the tissues of susceptible plants. Cell wall reinforcement and hormone signaling mechanisms seem therefore essential for a resistance response.